LESSONS LEARNED FROM CRITICAL SYSTEM FAILURES: A TECHNICAL OVERVIEW - SreenivasaRao Jagarlamudi (INTERNATIONAL JOURNAL OF ENGINEERING AND TECHNOLOGY RESEARCH (IJETR), 2024)
This article explores critical system failures across various technological domains, offering valuable insights for IT professionals, developers, and system architects. Through detailed case studies, it examines security breaches in Kafka clusters, disaster recovery failures, cryptographic vulnerabilities, and GPS accuracy issues in urban environments. The article highlights the increasing complexity and interconnectedness of modern IT systems, underscored by projected global IT spending of 4.5 trillion in 2023. It analyzes the financial and reputational impacts of these failures, with data breaches costing an average of 4.35 million in 2022. By dissecting these incidents, the article extracts key lessons and best practices for enhancing system security, implementing effective disaster recovery strategies, maintaining robust cryptographic practices, and improving GPS accuracy in challenging environments. The findings emphasize the critical need for proactive system design, rigorous security measures, and comprehensive testing in an era of rapidly evolving technological landscapes and sophisticated cyber threats